The use of macroalgae in feeds for finfish aquaculture - Hughes, Adam D.; Twigg, Gail C.; Msuya, Flower E.; Padmakumar, Krishna P.; Tocher, Douglas R. (Frontiers in Aquaculture, 2025)
Fed aquaculture accounted for around three-quarters of total aquaculture production in 2022. The most important raw materials in fish feed have traditionally been fishmeal and fish oil. Fishmeal has been the preferred protein source due to its high protein content and excellent amino acid profile. In aquaculture, feeds constitute over 50% of operating costs, with protein being the most expensive dietary source (based on inclusion levels). There is a growing need for alternative feed ingredients in securing the future supply of protein, as the high protein plant feedstuffs currently used are limited due to deficiencies in essential amino acids. Seaweeds have been cited as alternative protein sources for finfish with a quality of protein similar to traditional protein sources. The response of finfish to dietary seaweed is dose-dependent and species-specific, and any new protein source must be assessed on the provision of the most-limiting essential amino acid requirements of the target species. The potential of seaweed as an alternate protein or feed supplement ingredient in aquatic feeds has been well studied suggesting partial substitution of fishmeal up to 15% can be possible in most cases, although it may be higher in some species. While the majority of seaweed species contain insufficient levels of essential amino acids to meet the requirements of most finfish, despite their moderate protein contents, the number and levels of highly bioactive compounds and micro-nutrients in seaweed-derived products could be considered valuable and useful as functional additives for aquafeed fortification.